A geopolítica da Missão de Chiquitos : território, fronteiras e relações de espaço a partir da crônica de Juan Patricio Fernández (1726) - Santana, Juan Pablo Isoton de (2021)
This thesis investigates, from the chronicle written by the Jesuit Juan Patricio Fernández, in 1726, how the process of founding, development, and territorial construction of the Missions of Chiquitos, located in the eastern part of present-day Bolivia, took place. The Chiquitos reduction complex began in 1691, based on colonial references from the city of Santa Cruz de la Sierra and Colegio de Tarija, an institution linked to the Jesuitic Province of Paraguay. Considering the historical-geographic hypothesis that the document, in addition to the maps created at the time, operated a kind of territorialization, it is sought to understand how and in which ways this process of construction of space takes place, focusing on the diverse aspects interlaced to the problem. Among the issues mentioned, stand out those regarding the political linkage of the Jesus Society and its autonomy of action relating to the Monarchy of Spain; the nature of the borders; the internal colonial disputes for control over the native peoples between Jesuits and settlers from Santa Cruz de la Sierra and Asuncion; the conflicts regarding the Bandeirantes and the incessant efforts to enlarge the reductions, targeting the indigenous peoples in the region. Aligned to anthropology, and following the events narrated in the chronicle, it is intended to understand by use of which systems of technique and action the space of Chiquitos is created among the indigenous networks, or how the relations of space in the history of the Missions were updated, considering that the political relations and native territorial organization were the foundation for the making of this new colonial jurisdiction.